Studies of multicultural education in three last decades: global trends and future directions in educational researches - Sumargono, Sumargono; Sinaga, Risma Margaretha; Ariyani, Farida; Rini, Riswanti (Institute of Advanced Engineering and Science, 2024)
The publication trend regarding multicultural education studies has been increasing in three last decades. Nevertheless, systematic studies providing comprehensive bibliographic and bibliometric review related to this issue has not been performed nor also reported in the electronic journals or conference proceeding. A systematic review combined to bibliometric analysis was used to present global trends and future directions in educational researches related to multicultural education. 284 eligible documents from Scopus database published in 2001–2023 were involved as the data. Results revealed that in the period of 2001–2023, publication trend of multicultural education studies slightly soared while citation trend on the documents regarding multicultural education studies relatively fluctuated. The productive and influential documents, authors, countries, institutions, and sources contributed most to the development of multicultural education studies. Moreover, a lot of authors and institutions in the world jointly worked and also generated research networking in conducting the studies of multicultural education, mainly authors come from United States and educational institutions located in United States. Additionally, at least there are several major emerging themes related to multicultural education studies such as methodology, learning environment, main topic in multicultural education, affective and cognitive domain, participant, and theoretical framework. The future researches related to this topic should develop valid, practical, and effective learning models for multicultural competence referring to culturally responsive transformative teaching approach.